Class AB Voltage Follower and Low-Voltage Current Mirror with Very High Figures of Merit Based on the Flipped Voltage Follower - Jaime Ramírez-Angulo; Anindita Paul; Manaswini Gangineni; Jose Maria Hinojo-Montero; Jesús Huerta-Chua (Journal of Low Power Electronics and Applications, 2023)
The application of the flipped voltage follower to implement two high-performance circuits is presented: (1) The first is a class AB cascode flipped voltage follower that shows an improved slew rate and an improved bandwidth by very large factors and that has a higher output range than the conventional flipped voltage follower. It has a small signal figure of merit FOMSS = 46 MHz pF/µW and a current efficiency figure of merit FOMCE = 118. This is achieved by just introducing an additional output current sourcing PMOS transistor (P-channel Metal Oxide Semiconductor Field Effect Transistor) that provides dynamic output current enhancement and increases the quiescent power dissipation by less than 10%. (2) The other is a high-performance low-voltage current mirror with a nominal gain accuracy better than 0.01%, 0.212 Ω input resistance, 112 GΩ output resistance, 1 V supply voltage requirements, 0.15 V input, and 0.2 V output compliance voltages. These characteristics are achieved by utilizing two auxiliary amplifiers and a level shifter that increase the power dissipation just moderately. Post-layout simulations verify the performance of the circuits in a commercial 180 nm CMOS (Complementary Metal Oxide Semiconductor) technology.